2019
DOI: 10.1007/s41542-019-00045-1
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue, Secondary Traumatic Stress, and Vicarious Traumatization: a Qualitative Review and Research Agenda

Abstract: There has been growing research interest in what we term empathy-based stress, a process of traumatic stressor exposure, empathic experience, and adverse reactions among particular empathy-related professions, captured in the literatures on compassion fatigue, secondary traumatic stress, and vicarious traumatization in trauma-related lines of work. Although these three empathy-based strain constructs are highly related, each represents different components of similar strain responses. Unfortunately, extant rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 239 publications
(221 reference statements)
0
94
0
6
Order By: Relevance
“…The combination of secondary traumatic stress and burnout is commonly referred to as compassion fatigue [ 13 , 22 , 23 ]. Although the term is used synonymously with burnout [ 15 ], secondary traumatic stress [ 23 ], vicarious traumatisation [ 24 ] and traumatic countertransference [ 9 ], the present review focuses exclusively on compassion fatigue for the purpose of consistency and because some researchers have attempted to distinguish it from other similar constructs, e.g., [ 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of secondary traumatic stress and burnout is commonly referred to as compassion fatigue [ 13 , 22 , 23 ]. Although the term is used synonymously with burnout [ 15 ], secondary traumatic stress [ 23 ], vicarious traumatisation [ 24 ] and traumatic countertransference [ 9 ], the present review focuses exclusively on compassion fatigue for the purpose of consistency and because some researchers have attempted to distinguish it from other similar constructs, e.g., [ 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression, chronic health impairment and work-related stress have all been found to be associated with compassion fatigue [ 11 , 28 , 29 , 32 ]. In spite of this, the existing literature has paid more attention to the role of relatively stable individual-level characteristics (such as gender, age, history of trauma, negative life events, coping style and attachment style, among others) [ 22 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], as opposed to more dynamic, extrinsic and potentially alterable work-related factors. A relatively small body of research that has investigated the association of work-related factors has found that workload, client-related difficulties, relationships with other health professionals, emotional labour and support from supervisors and/or co-workers are some of the work-related factors that have been found to be associated with compassion fatigue in mental health professionals [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such second hand experiences may cause symptoms associated with PTSD, e.g., intrusive thoughts, or hyperarousal (Diehm et al, 2019 ). In recent research, it has been suggested that compassion fatigue, secondary traumatic stress, and vicarious traumatization can be grouped under the term empathy-based stress (Rauvola et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that VT, STS, and CF share common causes and consequences for service provision, these terms are understandably used interchangeably. However, many researchers have urged the conceptual differentiation of these constructs and some researchers have identified them as symptomatically different constructs (Molnar et al, 2017;Newell & MacNeil, 2010;Rauvola et al, 2019). Pearlman and Saakvitne (1995) defined VT as a change of cognitive schemas resulting from consistent empathic engagement with traumatized individuals (Newell & MacNeil, 2010).…”
Section: Vt Secondary Trauma Stress and Compassion Fatiguementioning
confidence: 99%